Leadership leaders, followers, and environments - Padilla, Arthur (John Wiley & Sons, 2013)
Padilla's Leadership brings a more holistic and comprehensive view to the leadership-followership process by focusing on all three of these critical aspects (leader, follower, organizational setting) something no other book on the market does.